2012
DOI: 10.1080/13504622.2011.572158
|View full text |Cite
|
Sign up to set email alerts
|

Free-choice learning suited to women’s participation needs in environmental decision-making processes

Abstract: United Nations mandates recognize the need to promote the full participation of women in environmental decision-making processes on the basis of gender equality. But, there remains a profound lack of effective women's participation in some sectors of environmental decision-making. Free-choice environmental learning offers an effective educational process for encouraging and developing such participation. This study outlines the shifts in and possibilities for women in environmental decision-making processes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…A number of studies have found that women frame problems and solutions in ways different from men. Partly, because women are socialized to be more empathic, caring of others and the environment, more interdependent and collectivistic, and are likely to be more adept at teamwork (Skanavis & Sakellari, 2008;Zelezny & Bailey, 2006;Zelezny et al, 2000;Gilligan, 1982). These attitudes and behaviors ultimately influence information processing and decision making, where women engage in decision making that is more effortful and comprehensive when compared to males engaged in selective information processes (Ramkissoon & Nunkoo, 2012).…”
Section: Gender Differencesmentioning
confidence: 99%
“…A number of studies have found that women frame problems and solutions in ways different from men. Partly, because women are socialized to be more empathic, caring of others and the environment, more interdependent and collectivistic, and are likely to be more adept at teamwork (Skanavis & Sakellari, 2008;Zelezny & Bailey, 2006;Zelezny et al, 2000;Gilligan, 1982). These attitudes and behaviors ultimately influence information processing and decision making, where women engage in decision making that is more effortful and comprehensive when compared to males engaged in selective information processes (Ramkissoon & Nunkoo, 2012).…”
Section: Gender Differencesmentioning
confidence: 99%
“…Tourism is a major contributor for the development of any nation. However, this "can also have ramifications, such as disrupting social structures, harming the socio-cultural authenticity of host communities, and threatening natural and cultural heritage" (Skanavis & Sakellari, 2008). The population needs to be educated on this so that the effects can be minimized and eradicated.…”
Section: Sustainable Development and Womenmentioning
confidence: 99%
“…The population needs to be educated on this so that the effects can be minimized and eradicated. Since women are engaged in many roles both in and out of the home, their "education and access to information are critical in order to acquire knowledge, develop the necessary skills and opportunities for participation in environmental decisions" (Skanavis & Sakellari, 2008). Prior studies indicate that women have a higher level of environmental concern and can play a huge role where safety is concerned especially at local level (Skanavis & Sakellari, 2008).…”
Section: Sustainable Development and Womenmentioning
confidence: 99%
“…In the tourism industry, the employment rate of women accounts for 46% compared with 43% employment in the economy (WTTC, 2019). Although, according to Skanavis and Sakellari (2008), gender inequality is still existing in tourism development. Thus, understanding citizen's perceptions of gender differences and improves knowledge, skills, and opportunities for women are the solutions to the problems.…”
Section: Literature Reviewmentioning
confidence: 99%